2022
DOI: 10.3390/app12125795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physiotherapy on Patients Suffering from COVID-19: An Observational Study

Abstract: Introduction: COVID-19 was the turning point of 2020, endangering the health of the entire population around the world. Among other therapeutic methods and supportive measures, physiotherapy represents a useful intervention applied on COVID-19 patients suffering from respiratory symptoms, this being supported by recent literature data. Materials and Methods: The study was performed on 45 patients diagnosed with COVID-19 (28 men, 17 women, mean age = 65.03, standard deviation = 14.83). They participated for 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pulmonary rehabilitation has many goals, such as maintaining flow through the respiratory tract, improving ventilation, decreasing the patient’s dyspnea, improving respiratory muscle function and chest mobility, reducing the respiratory rate, improving overall endurance, achieving relaxation with reduced or abolished anxiety and/or depression, and an overall improved quality of life for the patient [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation has many goals, such as maintaining flow through the respiratory tract, improving ventilation, decreasing the patient’s dyspnea, improving respiratory muscle function and chest mobility, reducing the respiratory rate, improving overall endurance, achieving relaxation with reduced or abolished anxiety and/or depression, and an overall improved quality of life for the patient [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also encourages physical activity, increases fitness, and supports a healthy lifestyle ( Brymer et al, 2010 ; Lawton et al, 2017 ). Studies have shown that time spent in nature positively affects mental and emotional health, reduces stress, improves mood, and encourages creativity ( Tinsley and Eldredge, 1995 ; Iwasaki et al, 2005 ; Li et al, 2021 ; Onu et al, 2022 ; Ratcliffe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%